Efficacy of ivermectin and albendazole combination in suppressing transmission of lymphatic filariasis following mass administration in Tanzania: a prospective cohort study - Adam M. Fimbo; Rajabu Hussein Mnkugwe; Eulambius Mathias Mlugu; Peter P. Kunambi; Alpha Malishee; Omary M.S. Minzi; Appolinary A. R. Kamuhabwa; Eleni Aklillu (BMC, 2024)
Abstract Background Preventive chemotherapy with ivermectin and albendazole (IA) in mass drug administration (MDA) programs for all at-risk populations is the core public health intervention to eliminate lymphatic filariasis (LF). Achieving this goal depends on drug effectiveness in reducing parasite reservoirs in the community to halt transmission. We assessed the efficacy of ivermectin and albendazole in clearing microfilariae and circulating filarial antigens (CFA) following MDA. Methods This community-based prospective study was conducted in Mkinga district, Tanga region, Tanzania, from November 2018 to June 2019. A total of 4115 MDA-eligible individuals were screened for CFA using Filarial test strips. CFA positives were re-examined for microfilariae by microscopy. CFA and microfilariae positive individuals were enrolled and received IA through MDA campaign. The status of microfilariae and CFA was monitored before MDA, and on day 7 and six-month following MDA. The primary efficacy outcomes were the clearance rates of microfilariae on day 7 and six-months, and CFA at 6 months of post-MDA. The McNemar test assessed the proportions of microfilariae positive pre- and post-MDA, while Chi-square tests were utilized to examine factors associated with CFA status six months post-MDA. Results Out of 4115 individuals screened, 239 (5.8%) tested positive for CFA, of whom 11 (4.6%) were also positive for microfilariae. Out of the ten microfilariae-positive individuals available for follow-up on day 7, nine tested negative, yielding a microfilariae clearance rate of 90% [95% confidence interval (CI): 59.6-98.2%]. Participants who tested negative for microfilariae on day 7 remained free of microfilariae six months after MDA. However, those who did not clear microfilariae on day-7 remained positive six-months post-MDA. The McNemar test revealed a significant improvement in microfilariae clearance on day 7 following MDA (P = 0.02). Out of 183 CFA-positive individuals who were available at 6-month follow-up, 160 (87.4%) remained CFA positive, while 23 became CFA negative. The CFA clearance rate at 6 months post-MDA was 12.6% (95% CI: 8.5-8.5%). There was no significant association of variability in ivermectin plasma exposure, measured by maximum concentration or area under the curve, and the clearance status of microfilariae or CFA post-MDA. Conclusions Preventive chemotherapy with IA effectively clears microfilariae within a week. However, it is less effective in clearing CFA at six months of post-MDA. The low clearance rate for filarial antigenemia underscores the need for alternative drug combinations and additional preventive measures to achieve LF elimination by 2030.